A Cryogenic Two Millimeter Receiver System - Chang Hoon Lee; Seong Tae Han; Yong Sun Park (Journal of Astronomy and Space Sciences, 1994)
Since we finished the purchase of the cooled Schottky diode mixer receiver made by Radiometer Physics Co. for the 120-170GHz range in October 1991, we have not prepared the PLL hardware and software for this receiver and the ellipsoidal mirror for beam guiding. After these problems were solved, this the confirmation of a spectral line detection and the measurement of the beam efficiency. The beam efficiency is about 36% at 146 GHz.